WhatsApp™ Seminar as Hoax Buster and Health Promotion Medium of COVID-19: A Field Trial - Fadilah, Mariatul; Liberty, Iche Andriani; Nadiah, Lathifah (Advances in Social Sciences Research Journal, 2020)
Accurate information and guidance on protective measures that can reduce the level of exposure to acute respiratory coronavirus 2 syndrome (SARS-CoV2) is the most important component in controlling the spread of coronavirus 2019 (COVID-19). As one of the largest social media in Indonesia, WhatsAppTM is a messaging service that is very close to the lives of Indonesian people, especially in the countryside. At the time of this research, no studies were published about using WhatsappTM as an Online Media used for the Seminar. This study aims to meet this information need and test its effectiveness as a health promotion medium, specifically Covid-19. The online seminar was conducted using WhatsAppTM media in the period 20 April 2020 - 30 April 2020. It was conducted 33 times in 33 groups, where each group was attended by an average of 176 participants, for 715 minutes and 724 questions. These groups present competent experts in their fields, and question and answer sessions are held between participants and experts. The results showed that 5,822 people who attended the seminar gave very positive feedback. The conclusions from the results of this field test show that WhatsAppTM can be an effective medium in health promotion to prevent transmission of COVID-19 in Indonesia.